Material requirements planning: application in small medium enterprise - Mohd Nor, Norasmiha; Cheam, Kai Wen; Ser, Eric Jun Hong; Cheng, Yung Tat; Lau, Wee Guan; Rokman, Nor Amira; Radin Abd Rahman, Raden Mohamad Salahuddin (Penerbit UTHM, 2020)
Production planning and control (PPC) refers to process that is used to plan and set up machines, human resource, and raw materials. In the separate operation in long-term view, PPC is the technique that used to plan every single step. The right decision of right time to do at the right place is needed to make using PPC to achieve efficiency in its maximation (Dr. F.C. Sharma, 2009).